Effect of Alkaline Peroxide-type Denture Cleaners to the Microbial Profile in Maxillary Complete Denture - Tarib, Natasya; Gan, Peijun; Tan, Mei Feng; Ahmad, Marlynda (UI Scholars Hub, 2018)
Objective: To investigate the effect of alkaline peroxide-type denture cleanser agents on the microbial profile, namely Streptococcus, Staphylococcus, and Candida species, in maxillary complete dentures. Methods: A total of 20 patients with maxillary complete dentures were recruited. Three denture cleanser agents were selected (n = 5): Polident® (P); Steradent® (S); and Pearlie White® (PW), with distilled water (DW) as control. Dentures were brushed before immersion with denture cleansers. Denture biofilm was collected from the palatal impression surface of the denture before and after immersion. The collected microorganisms were cultured and colony-forming units (CFU) were counted. Results: Significant reduction in the numbers of Streptococcus and Staphylococcus was observed after immersion with all denture cleanser agents (p< 0.05). On the other hand, no denture cleanser was significantly effective against Candida species ( p>0.05). Furthermore, S was more effective among other cleansers compared to DW (p< 0.05). Conclusion: Immersion of dentures in denture cleansers can reduce the amount of microorganisms on denture surfaces; thus, leading to effective denture hygiene. Steradent® denture cleanser showed the highest percentage reduction of polymicrobial organisms.